Rocking during sleep reduces motor deficits and beta-amyloid levels in an Alzheimer’s mouse model - Luyan Zhang; Letizia Santoni; Nam Anh Ngo; Reyila Simayi; Eleonora Ficiará; Luisa de Vivo; Michele Bellesi (iScience)
Summary: Alzheimer’s disease (AD) is a neurodegenerative disorder characterized by cognitive decline, beta-amyloid plaques, and tau tangles. Growing evidence suggests a strong link between sleep disturbances and AD progression, with disrupted sleep exacerbating AD progression through increased beta-amyloid and tau accumulation. This relationship indicates that improving sleep quality could slow disease progression and mitigate its effects on the brain. We investigated whether vestibular stimulation (rocking) could mitigate AD pathology in 3xTg mice (n = 58, males). Starting in early adulthood (p60), mice underwent 12-h daily rocking during the light period for four months. Rocking increased non-rapid eye movement (NREM) sleep initially, although habituation reduced this effect over time. Despite habituation, rocking slowed motor decline and reduced beta-amyloid levels in the cerebral cortex and hippocampus. However, tau levels remained unaffected. In conclusion, our findings highlight the potential of non-pharmacological methods to enhance NREM sleep and modify disease trajectory in AD models.